Analisis Pengaruh Struktur Modal, Aktivitas dan Likuiditas Terhadap Profitabilitas (Studi Pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI) - admin, TRESNA KIKI RATNASARI B1021131014 (Jurnal Manajemen Update, 2017)
This research entitled “Analysis of Influencing Capital Structure, Activity and Liquidity Towards Profitability (Study of Food and Beverage Company Registered in BEI)'' in the period 2011-2015. This research aims to know the influence of capital structure ratio, activity ratio and liquidity ratio towards profitability of food and beverages company in Indonesia Stock Exchange. Number of sample which was used 12 (twelve) food and beverages companies in IDX. Then, the method of collecting data was study documentation and literature review. Type of data was secondary data. And then,  method of analyzing data in this research was regression method of panel data and selection of estimation model used Eviews 7.The result of research showed that simultantly variable debt to equity ratio, total asset turn over and current ratio significantly influenced towards return on equity of food and beverage companies.  Partially, it was only variable debt to equity ratio which influenced toward profitability. Meanwhile,  the total of asset turn over and current ratio did not influence significantly toward return on equity. Keywords : profitability, structure capital, activity, and liquidity.